Environmental regulation and innovation in renewable energy technologies: Does the policy instrument matter? - Erik Hille; Wilhelm Althammer; Henning Diederich (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We examine how different renewable energy support policies affect innovation in solar and wind power technologies. The analysis is conducted using policy and patent data for a large sample of 194 countries and territories. The policy data allows distinguishing two dimensions of regulation, i.e. design and intensity, and their effects on innovation. The patent data is based on the new Y02E system and covers the period 1990 to 2016 with the more recent years of both strong increases and declines in patenting activity. The results show that, first, more intense portfolios of renewable energy support policies increase patenting in solar- and wind-power-related technologies. Second, this inducement effect is the strongest for public RD&D programs, targets, and fiscal incentives. In contrast to previous studies, this paper finds a consistently positive impact of feed-in tariffs and does not detect technology-specific differences in the effectiveness of this policy instrument. Third, the positive effect on patenting activity increases significantly over time with an increase in the duration of the implemented RD&D programs and targets.
Keywords: H23; O31; Q42; Q55; Q58; 330; Innovation; environmental regulation; renewable energy technologies; solar technologies; wind technologies